Are you simplifying the equation or solving for x?
Finding x:
You first expand the three terms in parenthesis, you do this by taking
5(x - 1) and multiplying 5 by x and -1 which gives 5x - 5, you repeat this for 6(x + 2), -7(x - 3) and 8(x + 1) which gives 6x + 12, -7x + 21 and 8x + 8
Collectively we have the equation 5x - 5 + 6x + 12 - 7x + 21 = 8x + 8
Next we group the like terms
5x + 6x - 7x
5 + 6 = 11 and 11 - 7 = 4, thus we have 4x and -5 + 12 + 21 = 28
Now the equation has been simplified to 4x + 28 = 8x + 8
Then we subtract each side by 28 which is 4x = 8x - 20
Then 8x is subtracted from each side, giving -4x = -20
Lastly both sides are divided by -4 to isolate x which gives x = 5
Fully simplified:
To have the equation fully simplified you just stop at 4x + 28 = 8x + 8 if it is an answer choice, if it is not factor the equation.
I will be using GFC (Greatest Common Factor) to factor.
We start factoring at turning 28 into 4 * 7
4x + 28 = 4x + 4 * 7
4 being the common factor gets factored out, leaving 4(x+7)
Repeat for 8x + 8, where 8x + 8 = 8 * 1, the common factor is 8 so you remove it giving the final simplification of:
4( x + 7 ) = 8( x + 1 )